Energetically and ecologically sustainable, affordable and healthy built environment - Irene Lill (International Journal of Strategic Property Management, 2018)
„Energetically and ecologically sustainable, affordable and healthy built environment” International Journal of Strategic Property Management, 22(4), p. 234-235.